STATE ADMINISTRATION OF JUDICIAL AUTHORITY QUALITY IN RUSSIA - Vadim N. Tsyganash (Advanced Engineering Research, 2011)
It is mentioned that the judicial authority relations cannot be considered out of state interests which being institutionally executed in the system of the legislation and the competence of public authorities are the integral part of the formation of the judicial-power relations. It is shown that in the course of forming the judicial act the political will and the state interest provide the development of social order.